The Factors Affecting Customer Loyalty At Conter Ervin Cell Bengkulu Selatan - Akbar Ilahi; Nia Indriasari; Eska Prima Monique (Journal of Indonesian Management, 2023)
Counter Ervin Cell Bengkulu Selatan is a shop that is engaged in selling Smartphones, selling cards and credits for all operators and serving Hardware, Software and Smartphone Accessories services "and is one of the businesses that prioritizes service to its customers.This type of research uses quantitative research. The method of analysis in this study uses Validity test, Reality test, Calsik Assumption Test, Multiple Linear Regression Analysis, Coefficient of Determination and hypothesis testing using t test. The number of samples studied was 96 96 questionnaires to buyers of goods at the Ervin cell counter.The results of the multiple linear regression analysis are Y = 7.639 + 0.265 X1 + 0.351 X2 + 0.232 X3, this describes a positive regression direction, meaning that the variables of customer quality (X1) and service quality (X2) and product quality (X3) have a positive influence. on customer loyalty (Y) at the Ervin cell Manna Bengkulu Selatan counter. The value of the coefficient of determination from the results of calculations using SPSS can be seen that the value of the coefficient of determination from R square is 0.617. This means that the value of customer quality (X1) and the value of service quality (X2) and product quality (X3) affect customer loyalty (Y) by 61.7% while the remaining 29.3% is influenced by other variables not examined in the study this.